Bilateral lung transplantation for pediatric pulmonary arterial hypertension: perioperative management and one-year follow-up - Jack, Thomas; Carlens, Julia; Diekmann, Franziska; Hasan, Hosan; Chouvarine, Philippe; Schwerk, Nicolaus; Müller, Carsten; Wieland, Ivonne; Tudorache, Igor; Warnecke, Gregor; Avsar, Murat; Horke, Alexander; et al. (Frontiers in Cardiovascular Medicine, 2023)
Background: Bilateral lung transplantation (LuTx) remains the only established treatment for children with end-stage pulmonary arterial hypertension (PAH). Although PAH is the second most common indication for LuTx, little is known about optimal perioperative management and midterm clinical outcomes. Methods: Prospective observational study on consecutive children with PAH who underwent LuTx with scheduled postoperative VA-ECMO support at Hannover Medical School from December 2013 to June 2020. Results: Twelve patients with PAH underwent LuTx (mean age 11.9 years; age range 1.9-17.8). Underlying diagnoses included idiopathic (n = 4) or heritable PAH (n = 4), PAH associated with congenital heart disease (n = 2), pulmonary veno-occlusive disease (n = 1), and pulmonary capillary hemangiomatosis (n = 1). The mean waiting time was 58.5 days (range 1-220d). Three patients were bridged to LuTx on VA-ECMO. Intraoperative VA-ECMO/cardiopulmonary bypass was applied and VA-ECMO was continued postoperatively in all patients (mean ECMO-duration 185 h; range 73-363 h; early extubation). The median postoperative ventilation time was 28 h (range 17-145 h). Echocardiographic conventional and strain analysis showed that 12 months after LuTx, all patients had normal biventricular systolic function. All PAH patients are alive 2 years after LuTx (median follow-up 53 months, range 26-104 months). Conclusion: LuTx in children with end-stage PAH resulted in excellent midterm outcomes (100% survival 2 years post-LuTx). Postoperative VA-ECMO facilitates early extubation with rapid gain of allograft function and sustained biventricular reverse-remodeling and systolic function after RV pressure unloading and LV volume loading.
Gesehen am 22.08.2023